2014
DOI: 10.5653/cerm.2014.41.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell-penetrating peptide-conjugated estrogen-related receptor β on the development of mouse embryos culturedin vitro

Abstract: ObjectiveEstrogen related receptor β (Esrrb) is a member of the orphan nuclear receptors and may regulate the expression of pluripotency-related genes, such as Oct4 and Nanog. Therefore, in the present study, we have developed a method for delivering exogenous ESRRB recombinant protein into embryos by using cell-penetrating peptide (CPP) conjugation and have analyzed their effect on embryonic development.MethodsMouse oocytes and embryos were obtained from superovulated mice. The expression of Oct4 mRNA and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This concentration was previously determined in experiments testing the efficacy of the protein on unfrozen mouse embryos. 27 Our results revealed that CPP-ESRRB penetrated into both the cytoplasm and the nuclei of embryos by 24 hours posttreatment and that this protein was maintained by 48 hours (Figure 3A). Furthermore, the total ESRRB protein level was much higher in blastocysts of the CPP-ESRRB-treated group compared to the untreated group (Figure 3B).…”
Section: Resultsmentioning
confidence: 65%
“…This concentration was previously determined in experiments testing the efficacy of the protein on unfrozen mouse embryos. 27 Our results revealed that CPP-ESRRB penetrated into both the cytoplasm and the nuclei of embryos by 24 hours posttreatment and that this protein was maintained by 48 hours (Figure 3A). Furthermore, the total ESRRB protein level was much higher in blastocysts of the CPP-ESRRB-treated group compared to the untreated group (Figure 3B).…”
Section: Resultsmentioning
confidence: 65%
“…Support for this strategy is provided by our previous report showing that CPP-conjugated ESRRB, a member of the orphan nuclear receptor families, improved the developmental potential of cryopreserved mouse embryos and increased expression of the transcription factors Oct4 and Nanog 25 . In addition, supplementation of culture medium with CPP-ESRRB protein has been shown to enhance the function of ICM in fresh embryos increasing Oct4 gene expression 24 . Consistent with these observations, we here found that treatment of embryos with CARM1 protein improved the TE development and enhanced the quality of cloned embryos through epigenetic modification.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining was as described previously 24 with slight modifications. Briefly, the zona-pellucida of the embryo was removed using acidic Tyrode’s solution (Millipore).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations